Mobile applications and solutions for social inclusion - Paiva, Sara, 1979- (Information Science Reference, 2018)
"This book explores indoor navigation, tracking and monitoring, context-aware, alert systems, development enhancements, payments, etc. It contains case studies and practical mobile applications that clearly contribute for advances in the field of social inclusion"--